Soft-law and protection of trans people in Europe (TEST BioLaw Journal - Rivista di BioDiritto, 2024)
The essay considers hard-law legislation for the protection of trans people, but focuses its attention on the soft-law instruments which, over the years, have integrated the principles and rules regarding the rights of trans people. With a critical intent, this text examines the contribution in which this particular area of law regulation has contributed to the increase in trans people protection, as well as the role that soft-law has today to face the main challenges of the current events.
Keywords: Soft-law; hard-law; integrazione europea; persone trans; diritti fondamentali